2018
DOI: 10.3168/jds.2017-12828
|View full text |Cite
|
Sign up to set email alerts
|

Describing temporal variation in reticuloruminal pH using continuous monitoring data

Abstract: Reticuloruminal pH has been linked to subclinical disease in dairy cattle, leading to considerable interest in identifying pH observations below a given threshold. The relatively recent availability of continuously monitored data from pH boluses gives new opportunities for characterizing the normal patterns of pH over time and distinguishing these from abnormal patterns using more sensitive and specific methods than simple thresholds. We fitted a series of statistical models to continuously monitored data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 18 publications
(16 reference statements)
1
34
0
Order By: Relevance
“…To reduce the noise caused by extraneous movements of cattle, a night-only data-frame was established using observations recorded from 21 : 00 until 07 : 00. The pH data were analysed using the method described in Denwood et al (2018) to generate a list of predicted values for each animal according to a generalized additive model fitted with a single sine-wave. For each predicted value, the residual was calculated, and the absolute value of the residual was used for the subsequent analysis.…”
Section: Statistical Analysis: Reticuloruminal Ph and Motilitymentioning
confidence: 99%
“…To reduce the noise caused by extraneous movements of cattle, a night-only data-frame was established using observations recorded from 21 : 00 until 07 : 00. The pH data were analysed using the method described in Denwood et al (2018) to generate a list of predicted values for each animal according to a generalized additive model fitted with a single sine-wave. For each predicted value, the residual was calculated, and the absolute value of the residual was used for the subsequent analysis.…”
Section: Statistical Analysis: Reticuloruminal Ph and Motilitymentioning
confidence: 99%
“…Moreover, to evaluate subsequent periods in which acidosis might occur, absence of interaction between initial pH level and individual response to a subsequent change in intake or diet composition has to be assumed. Similar to the individual animal approach of Villot et al (2018), Denwood et al (2018) distinguished long-term temporal pH variation by using a generalized additive model, reflecting gradual pH changes due to diet or pH sensor drift, and short-term cyclical pH variation by using a sine wave with daily frequency and a sine wave with milking frequency. Upon application of this statistical approach, they showed that deviations from a predictable daily pH rhythm were associated with decreased DMI and milk production of dairy cattle.…”
Section: Data Analysis Methods and Data Interpretationmentioning
confidence: 99%
“…Such significant drift of indwelling rumen sensors that cannot be retrieved and recalibrated is a major obstacle to their use. Long-term drift may be quantified by calculating moving averages (Villot et al, 2018) or using a generalized additive model (Denwood et al, 2018) for individual animals. However, drift established in this way is confounded with any long-term, slow change in ruminal pH due to gentle, consistent variation in voluntary feed intake, feed intake behaviour or gentle dietary changes.…”
Section: Sensor Driftmentioning
confidence: 99%
“…The condition also occurs in beef cattle (Nagaraja & Titgemeyer, 2007). The diagnosis and management of SARA is difficult, as there is little consensus on diagnostic criteria and it is largely a chronic predisposition to other specific diseases, rather than being a single disease entity itself (Kleen et al, 2009, Denwood et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…From studies with dairy cattle, it is known that some farms are more susceptible to acidosis than others, and that within herds some animals are more prone to acidosis than others (Garrett, 1996;Kleen et al, 2009;Morgante et al, 2007;Penner et al, 2009;Denwood et al, 2018). Many of the experimentally determined interactions among feeding methods, feed and animal behaviour in feedlots have been reviewed elsewhere (e.g.…”
Section: Introductionmentioning
confidence: 99%